Kinematic synthesis and analysis of planar crank slider and slider slider mechanisms. - Hernandez, Manuel V. Jr. Ph D (Philippine Engineering Journal)
Synthesis and analysis equations are formulated for the planar crank slider and the slider slider mechanisms using motion parameters based on displacements from the initial position of the mechanisms. The synthesis equations are derived explicitly in terms of these parameters and also the parameters describing the mechanisms at their initial positions. These synthesis equations are generalized for Multiply-Separated Position Synthesis. The solutions to the resulting systems of non-linear equations are shown for different cases of number of positions and unknowns and specified parameters describing the mechanisms at their initial positions.